Review of Urinary Tract Infections in Pregnancy: Risks, Complications and Management - Kałuziak, Patrycja; Parys, Jakub; Mikosińska, Agnieszka; Kaźmierczak, Martyna; Jajczak, Marta; Mossakowski, Maciej; Witek, Aleksandra; Litwin, Mateusz; Jesionek, Stanisław (Quality in Sport, 2025)
Background: Urinary tract infections (UTIs) are common in pregnant women due to significant changes during gestation. UTIs can affect any part of the urinary system and are typically caused by bacteria, though fungi and viruses can also be responsible. Asymptomatic bacteriuria (ASB is frequent in pregnancy and must be treated to prevent serious maternal and fetal complications. Routine screening for ASB is standard in prenatal care, and treatment with safe, effective antibiotics is essential. Preventive strategies also help reduce UTI during pregnancy. Aim of the study: The study aimed to explore the changes that occur during gestation, which predispose pregnant women to UTIs, assess the diagnostic methods and select the most effective treatment to prevent complications. State of knowledge: Urinary tract infections (UTIs) are common perinatal complications, with higher prevalence in pregnancy due to changes that occur during gestation. UTIs can perform as asymptomatic bacteriuria (ASB), cystitis and pyelonephritis, which can result in severe complications. Clinical guidelines recommend screening for ASB in early pregnancy and prescribing a short course of antibiotics if detected. Escherichia coli is the most common cause of UTIs. As most antibiotics cross the placenta, treatment must be safe for the fetus and effective against the pathogens. Guidelines recommend short courses of antibiotics. Conclusions: UTIs in pregnancy are common and lead to serious complications if untreated. Pregnant women are more susceptible to UTIs due changes that occur during gestation. Healthcare professionals play a critical role in managing UTIs during pregnancy. Early detection through routine screening and prompt treatment is crucial for optimal outcomes. Healthcare professionals, including obstetricians, should educate patients on preventive measures and recognizing early UTI symptoms. Abbreviations: UTIs- urinary tract infections; ASB- asymptomatic bacteriuria